2018
DOI: 10.14406/acu.2018.028
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Thread Embedding Therapy of Knee Osteoarthritis

Abstract: Objectives : This study was performed to review the efficacy of national and international randomized controlled trials (RCTs) investigating evidence on thread embedding therapy for knee osteoarthritis. Methods : Online databases (PubMed, EMBASE, Cochrane, NDSL, OASIS, CNKI) were searched for studies where thread embedding therapy was performed for Knee Osteoarthritis from their inception to July 2018. Two researchers independently performed the search. Only RCTs were selected. Eligible studies were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…It is a special method of treatment involving acupuncture, in which polydioxanone is injected into the subcutaneous or muscle layer at specific acupoints, which provides longlasting pain control effect compared to dry needling. 11,12 The pain control mechanism of TEA is medicated via the Sig-1R receptor and mitogen-activated protein kinase (MAPK) or spinal serotonin 1A receptor, and the GluN1 subunit of N-methyl-d-aspartate receptor (NMDA). As TEA inhibits MAPK p38 in the spinal cord, it can also alleviate pain induced by complete Freund's adjuvant's inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is a special method of treatment involving acupuncture, in which polydioxanone is injected into the subcutaneous or muscle layer at specific acupoints, which provides longlasting pain control effect compared to dry needling. 11,12 The pain control mechanism of TEA is medicated via the Sig-1R receptor and mitogen-activated protein kinase (MAPK) or spinal serotonin 1A receptor, and the GluN1 subunit of N-methyl-d-aspartate receptor (NMDA). As TEA inhibits MAPK p38 in the spinal cord, it can also alleviate pain induced by complete Freund's adjuvant's inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 [ 1 , 18 , 23 – 26 ] and Table 3 [ 1 , 22 , 27 , 28 ] summarize of the details of TEA and EA treatments. The subjects in the (TEA + EA + Usual care) group will receive the combined treatment consisting of TEA once a week and EA twice a week for 4 weeks while continuing usual care.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] TEA is used for neck pain, [ 14 ] low back pain, [ 15 ] shoulder pain, [ 16 ] and for sequelae of facial paralysis. [ 17 ] A systematic literature review on TEA for degenerative KOA [ 18 ] included 3 randomized controlled trials published in China, and all 3 studies showed significant therapeutic effects in the intervention group that received TEA. EA involves the application of electrical stimulation along with acupuncture stimulation, and is widely used in clinical practice to relieve acute or chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Open access intervertebral disc and osteoarthritis and internal diseases such as abdominal obesity, non-alcoholic fatty liver disease and gastro-oesophageal reflux disease. [9][10][11][12][13] Acupuncture has generally been known as a safe treatment method with minimal risk of adverse events (AEs) to patients. The York Acupuncture Safety Study conducted in 2001 analysed 34 407 cases of the acupuncture treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%